2010
DOI: 10.1007/s10750-010-0128-8
|View full text |Cite
|
Sign up to set email alerts
|

Identifying hybridizing taxa within the Daphnia longispina species complex: a comparison of genetic methods and phenotypic approaches

Abstract: Daphnia galeata Sars, D. longispina O. F. Müller and D. cucullata Sars (Crustacea: Cladocera) are closely related species which often produce interspecific hybrids in natural populations. Several marker systems are available for taxon determination in this hybridizing complex, but their performance and reliability has not been systematically assessed. We compared results from identifications by three molecular methods. More than 1,200 individuals from 10 localities in the Czech Republic were identified as pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 64 publications
2
32
0
1
Order By: Relevance
“…Evidence of introgression of ITS1 alleles among species of the D. longispina complex was recently reported (Gießler & Englbrecht, 2009). Similarly, Dlouhá et al (2010) observed that substantial deviations in identifications by ITS-RFLP and other methods may occur in some reservoir populations; in particular, D. galeata 9 longispina hybrids were overestimated at some localities. However, the discrepancy between the two molecular methods (ITS-RFLP and allozyme electrophoresis) should not have substantially affected our results.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Evidence of introgression of ITS1 alleles among species of the D. longispina complex was recently reported (Gießler & Englbrecht, 2009). Similarly, Dlouhá et al (2010) observed that substantial deviations in identifications by ITS-RFLP and other methods may occur in some reservoir populations; in particular, D. galeata 9 longispina hybrids were overestimated at some localities. However, the discrepancy between the two molecular methods (ITS-RFLP and allozyme electrophoresis) should not have substantially affected our results.…”
Section: Discussionmentioning
confidence: 84%
“…However, the discrepancy between the two molecular methods (ITS-RFLP and allozyme electrophoresis) should not have substantially affected our results. Both methods were intercalibrated for populations from all but one (Ž lutice) of the studied reservoirs and showed 89-96% agreement (Dlouhá et al, 2010), and differences between the composition of active Daphnia populations and resting egg banks in Ž lutice did not show any suspiciously deviating patterns.…”
Section: Discussionmentioning
confidence: 93%
“…As reference parental species, we used 40 well-defined genotypes of D. cucullata , D. galeata and D. longispina , originating from 23 locations in Europe and one location in North America, which were also classified using two allozyme loci, recognised to be diagnostic for species identification [33,43]. For detailed information about those genotypes see [18].…”
Section: Methodsmentioning
confidence: 99%
“…Allozyme electrophoresis can be applied to fresh or frozen animals, but not to diapausing eggs. In contrast, microsatellite analysis can be applied to both, but the knowledge about speciesspecific alleles is limited (Brede et al 2006;Dlouhá et al 2010). Allozyme electrophoresis was performed, as described by Keller and Spaak (2004), using the two speciesspecific loci aspartate amino transferase (enzyme commission number [EC] 2.6.1.1) and aldehyde oxidase (EC 1.2.3.1).…”
Section: Methodsmentioning
confidence: 99%